2009
DOI: 10.1590/s0006-87052009000300009
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and expected selection gain for growth traits in Eugenia dysenterica DC. populations

Abstract: The objective of this study was to estimate genetic parameters of quantitative traits in a living germplasm collection of Eugenia dysenterica. The genetic material consisted of 110 progenies derived from 10 natural Eugenia dysenterica subpopulations sampled in the southeastern region of the state of Goiás. The experiment was established in a complete randomized block design, with 110 treatments, four replications and one tree per plot. The study variables were total height, stem diameter and respective growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 8 publications
1
11
1
1
Order By: Relevance
“…This indicates that the difference between the bifurcation pattern between individuals is caused simply by random environmental variables that are not structured in any hierarchical level. This result corroborates Aguiar et al (2009), who worked with quantitative traits from the same individuals of the germplasm collection. On the occasion, the authors found that the plant height and stem diameter at 30 cm from the ground only had significance for the proportion of variation between subpopulations in the first year of assessment.…”
Section: Subpopulations Location Tree Variables Leaf Variables H (M) supporting
confidence: 87%
See 3 more Smart Citations
“…This indicates that the difference between the bifurcation pattern between individuals is caused simply by random environmental variables that are not structured in any hierarchical level. This result corroborates Aguiar et al (2009), who worked with quantitative traits from the same individuals of the germplasm collection. On the occasion, the authors found that the plant height and stem diameter at 30 cm from the ground only had significance for the proportion of variation between subpopulations in the first year of assessment.…”
Section: Subpopulations Location Tree Variables Leaf Variables H (M) supporting
confidence: 87%
“…Aguiar et al (2009) observed that progenies reached, at four years of age, on average, 1.68 m height, with annual average growth of 0.38 m. Based on this growth rate, it would be expected, after 13 years, that the progenies had an average height of 4.94 m, assuming a linear growth. The expected value is very close to that registered in this study, which indicates that the growth rate observed in the first four years of age can be used to predict the plant height until at least the first 13 years.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Alguns trabalhos relacionados aos óleos essenciais (DUARTE et al, 2009;2010) e genética e melhoramento (AGUIAR et al, 2009;CHAVES et al, 2011) têm sido abordados recentemente. No entanto, não se tem conhecimento, em condição de cultivo, sobre a duração da fase imatura até a cagaiteira de pé-franco entrar na fase reprodutiva.…”
Section: Initial Fruiting Of the Cagaita Tree (Eugenia Dysenterica DCunclassified